Entry Deterrence - Roger Ware (Queen's University, Department of Economics, 1991)
This paper surveys the recent literature on strategic entry deterrence. Particular attention is paid to limit pricing, entry deterrence models using a two-stage framework, incomplete information treatments of entry deterrence and entry deterrence as a framework for modeling the determination of market structure. In addition there is some discussion of antitrust issues.
Keywords: 330